Effect of bone cement distribution on adjacent disc degeneration after vertebral augmentation for osteoporotic vertebral compression fractures in aging patients - Zhang, Zhen; Zhang, Jialang; He, Baorong; Dong, Qi; Hao, Dingjun (Frontiers in Surgery, 2023)
Background: The influence of vertebral augmentation on adjacent intervertebral discs remains controversial. The purpose of this study is to evaluate the effect of bone cement distribution on adjacent disc degeneration after vertebral augmentation for osteoporotic vertebral compression fractures (OVCFs). Methods: Patients with single level OVCF and upper endplate injury who underwent vertebral augmentation were enrolled. The patients were divided into four groups: Group A: bone cement contacted both the cranial and the distal endplates; Group B: bone cement only contacted the cranial endplate; Group C: bone cement only contacted the distal endplate; and Group D: bone cement contacted neither the cranial nor the distal endplates. The cranial discs of the fractured vertebrae were defined as adjacent discs and the upper discs proximally to the adjacent discs were defined as control discs. Degenerative disc change (DDC) was defined as a deteriorated postoperative Pfirrmann score compared with the preoperative score on MR images. The number of DDC cases and the disc heights were analyzed among the groups. Results: A total of 184 patients with an average follow-up time of 28.6 months were included. The number of DDC cases in the adjacent discs was significantly higher than in the control discs in groups A (p<0.001), B (p=0.002), and D (p=0.028), whereas the difference in group C was not statistically significant (p=0.237). The incidence of adjacent disc degeneration was significantly higher in group A than that in group C (p=0.06). The adjacent disc heights decreased significantly in groups A, B, and D (p<0.001, p<0.001, and p=0.012, respectively), but did not decrease significantly in group C (p=0.079). However, no statistical differences were detected among the four groups with respect to the preoperative adjacent disc height, follow-up adjacent disc height, preoperative control disc height, or follow-up control disc height. Conclusion: Bone cement distribution influences adjacent disc degeneration after vertebral augmentation in OVCFs. Cement distribution proximal to the injured endplate can accelerate adjacent disc degeneration, and cement in contact with both the cranial and distal endplates can induce a higher incidence of adjacent disc degeneration.